PENGARUH PEMAHAMAN E-COMMERCE TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI DPIB SMK NEGERI 7 BALEENDAH TAHUN AJARAN 2021-2022 - Taufiq Hafiyyan, - (2022)
In this rapid development there is an e-commerce platform, namely marketing using electronic media using the internet which is used for business by groups, individuals and students can use this e-commerce platform, at SMK Negeri 7 Baleendah there are entrepreneurship lessons that aim to develop interest in entrepreneurship, the existence of a continuing learning program through entrepreneurship (BMW) which is to cultivate vocational school graduates to become entrepreneurs. The aims of this study were to (1) determine the understanding of e-commerce by class XI DPIB students at SMK Negeri 7 Baleendah, (2) Entrepreneurial Interests in Class XI students at DPIB SMK Negeri 7 Baleendah in the academic year 2021/2022 (3) to determine the effect of understanding e-commerce Against Entrepreneurial Interests in Class XI DPIB SMK Negeri 7 Baleendah. The approach in this research is descriptive quantitative survey method is used, by carrying out the processing of parametric statistical data, the data collection process is carried out by distributing multiple choice tests and distributing questionnaires. Involving the entire population of class XI DPIB SMK Negeri 7 Baleendah students with a research sample of 50 students and a trial sample of 20 students. In this study, it was stated that (1) Students' understanding of E-Commerce was in the high category by percentage of 44% (2) Student's Entrepreneurial Interest in the medium category by percentage of 36% (3) Students' understanding of e-commerce had a significant influence on the entrepreneurship interest of class XI DPIB SMK Negeri 7 Baleendah students. Keywords: E-commerce, Interest in Entrepreneurship, Vocational High School.